Nutrient Content, Organoleptic Quality, and Shelf Life of Sagon Substitute From Lindur (Bruguiera gymnorrhiza L.) and Soybean Flour (Glycine max L.), as an Alternative Emergency Food - Afifah, Diana Nur; Ningrum, Yesi Pratama Aprilia; Syahidah, Tazkiah; Nuryanto, Nuryanto; Ayustaningwarno, Fitriyono; Sugianto, Denny Nugroho (Frontiers in Nutrition, 2022)
Lindur (Bruguiera gymnorrhiza L.) fruit as a mangrove species has not been widely developed. However, the combination of Lindur fruit functional food with soybean flour has high carbohydrates and protein potential to serve as an additional food product in emergency conditions. Therefore, this study aims to evaluate the nutritional content, dietary fiber, organoleptic quality, and Sagon shelf life estimation of Lindur and soybean flour, in accordance with emergency food quality requirements. The shelf life was determined using the Accelerated Shelf life Testing (ASLT) method with the Arrhenius equation, where the sample was stored in an incubator at a temperature of 27oC, 37oC, as well as 47oC for 30 days, and the water content, peroxide number, and free fatty acid content were tested every 5 days. In addition, formulation P1 comprising 45% Lindur flour and 35% soybean flour was discovered to be the best formulation, with a composition of 251.5 kcal/bar of energy, 6.3 grams of fat, 4.4 grams of protein, 30 grams of carbohydrates, 15.79% dietary fiber, 1.84% ash content, and 4.03% water content. Therefore, the nutritional content of Sagon substitution for Lindur flour is in accordance with the emergency food quality requirements, except for the protein content. Also, the P2 Sagon sample’s shelf life was estimated to be 37 days in polypropylene plastic packaging at room temperature of 27oC.